Long‐term follow‐up of anterior vaginal repair: A comparison among colporrhaphy, colporrhaphy with reinforcement by xenograft, and mesh. Issue 1 (2nd May 2017) - Balzarro, Matteo; Rubilotta, Emanuele; Porcaro, Antonio B.; Trabacchin, Nicolò; Sarti, Alessandra; Cerruto, Maria A.; Siracusano, Salvatore; Artibani, Walter
Abstract : Aims: To assess the long‐term complications and outcomes in patients treated for pelvic organ prolapse (POP) with transvaginal anterior colporrhaphy (AC) alone, transvaginal naterior AC with reinforcement by using porcine Xenograft (AC‐P) (Pelvisoft® Biomesh), and transvaginal anterior repair with polypropylene mesh (AC‐M). Methods: This was a retrospective analysis of 109/123 consecutive patients, who underwent cystocele repair: 42 AC, 19 AC‐P, and 48 AC‐M. Subjective outcomes included validated questionnaires as well as questions that had not been previously validated. Objective outcomes have been evaluated considering failure the anterior vaginal wall recurrence >2 stage POP‐Quantification. Statistical analysis included the chi‐square or Fisher exact test. Results: The mean follow‐up was 94.80 ± 51.72 months (19‐192 months). In all groups, the patient's personal satisfaction was high. There was no evidence of difference in outcome based on whether a biological graft was or was not performed, or whether synthetic mesh was used to reinforce the repair. Data showed a higher rate of complications in the AC‐M group ( P < 0.05) that could explain the lower subjective satisfaction of these patients. Conclusions: This study evaluated long‐term outcomes to anterior vaginal repair over a period of more than 5 years in all the groups. Our data show that anterior vaginal repair with mesh and xenograft did not improve significantly objective and subjective outcomes. Rather, prosthetic device use leads to higher rate of complications.